Continuous Support from the Same Public Health Nurse and Parental Perception and Use of Health Care Services: A Retrospective Observational Study - Yokoyama, Yoshie; Ogata, Yasue; Suzuki, Kimie; Kanaoka, Setsuko; Furushou, Kumi; Masuda, Reiko; Horiuchi, Sayaka; Yamagata, Zentaro; Kondo, Naoki; Silventoinen, Karri (Maternal and child health journal, 2024)
Objective Continuity is considered essential for high-quality maternal and child health care services, but studies to show this effect on parental well-being are still rare. We studied whether receiving support from the same public health nurse has a beneficial effect on parental perceptions of health care professionals and the use of childcare support services. Methods Maternal and child health care services were provided by different nurses in a Japanese municipality until March 2019. From April 2019, all families with infants received continuous support from the same assigned nurse. A questionnaire covering parental perception and the use of services was sent by postal mail to 1,341 families with infants. The data were analyzed using χ 2 -test, t-test and logistic regression producing odds ratios (OR) with 95% confidence intervals (CI). Results Parental perceptions of the availability of professionals to discuss children’s issues, the degree of understanding about available other childcare support services, the degree of utilizing other services, and satisfaction with health care services were higher in parents who received continuous support from the same assigned nurse compared to those who did not receive continuous support. Continuous support was associated with parental perceptions of the availability of professionals to discuss children’s issues (OR = 1.97, 95% CI 1.34–2.91) and the degree of understanding about available other child-care support services (OR = 1.65, 95% CI 1.11–2.44) after adjusting the results for socioeconomic factors. Conclusions Continuous support from the same assigned nurse has benefits for parents. This offers a cost-effective way to improve parental well-being. Significance What is Already Known on this Subject? Continuity is regarded as important in maternal and child health care. Parental perceptions of professionals are typically better if parents receive support from the same midwife. What this Study adds? Parents who received support from the same assigned public health nurse had better perceptions of professionals and understanding of childcare support services than parents who received support from different nurses even when the number of visits did not differ. Having support from the same assigned nurse increases parental well-being without the need for additional resources.